Green Tea Polyphenols and Sulfasalazine have Parallel Anti-Inflammatory Properties in Colitis Models - Oz, Helieh S.; Chen, Theresa; de Villiers, Willem J. (Frontiers in Immunology, 2013)
Background: There is no cure for autoimmune chronic inflammatory bowel disease (IBD). IBD patients commonly use complementary and alternative medications of which the safety, efficacy and interaction with standard-of-care therapies are not fully known. Thus the consequences can become life-threatening. Sulfasalazine commonly used in IBD, potentially has severe adverse effects, including infertility, pulmonary fibrosis, lack of response and ultimately patients may require intestinal resection. We hypothesized that green tea polyphenols (GrTP, EGCG) and sulfasalazine have similar anti-inflammatory properties. Methods: BALB/c mice received Dextran sodium sulfate (DSS) to induce colitis (ulcerative colitis model). Exposure of IL-10 deficient mice (BALB/c-background) to normal microbiota provoked enterocolitis (mimics Crohn’s disease). Animals were treated with agents incorporated into daily diets. Control animals received sham treatment. Results: DSS-treated animals developed severe bloody diarrhea and colitis (score 0-4, 3.2+0.27). IL-10 deficient mice developed severe enterocolitis as manifested by diarrhea, rectal prolapse and colonic lesions. Animals tolerated regimens (GrTP, EGCG, sulfasalazine) with no major side effects, and further developed less severe colitis/enterocolitis. GrTP, EGCG and sulfasalazine significantly ameliorated colonic damage and histological scores in treated animals in a similar manner (GrTP vs DSS p<0.05; EGCG, sulfasalazine vs DSS p<0.01). The inflammatory markers TNFα (3-fold), IL-6 (14-fold) and serum amyloid A (40-fold) increased in colitic animals and significantly decreased with treatment regiments. In contrast, circulatory leptin levels decreased in colitic animals (2-fold). EGCG additionally reduced leptin levels (p<0.01) while GrTP and sulfasalazine had no effect on leptin levels (p<0.05). Hepatic and colonic antioxidants were significantly depleted in colitic animals and treatment regiments significantly restored antioxida